An investigation on the uncertainty of fill factor - Pavanello Diego; Sample Tony; Müllejans Harald (EPJ Photovoltaics)
This study focuses on the fill factor (FF) measurement uncertainty contributing to the uncertainty in the labeling of the nominal maximum power (Pmax) of photovoltaic modules, which is determined under Standard Test Conditions (STC). Given that the price of these modules is tied to their Pmax, accurately quantifying the uncertainty of this measurement is crucial for ISO/IEC 17025 accredited laboratories. Adhering to the “Guide to the expression of uncertainty in measurement”, this work evaluates the uncertainty contribution of the Fill Factor (FF), a key parameter linking Pmax, the open-circuit voltage (Voc), and the short-circuit current (Isc). The analysis is based on data from three reference modules measured at the European Solar Test Installation (ESTI), part of the Joint Research Centre of the European Commission, since 1996. This data shows a reduction in FF uncertainty from approximately 0.6% to 0.3%, attributed to advancements in measurement technologies and techniques. Considering the goal of top calibration laboratories to measure Pmax with the lowest possible uncertainty, the improvement in FF uncertainty measurement is significant, ensuring more accurate labeling of photovoltaic modules.